STUDY ON ULTRASONIC EVALUATION METHOD OF THE POROSITY IN CARBON FIBER COMPOSITE MATERIAL - CHEN XianTao; DENG YanYan; REN WenJian (Jixie qiangdu)
Pore is one of the most common internal defects for a carbon fiber composite material, the size and distribution of the pore have a significant impact on the mechanical properties of carbon fiber composite material. Based on the extrusion molding of carbon fiber unidirectional reinforced composites as the test object, by using the ultrasonic attenuation and nonlinear ultrasonic testing methods for the comparing three different porosity of samples, extract the characteristics of the ultrasonic testing parameters, implementation of carbon fiber composite materials characterization of porosity size.